Insecticide activity and phytochemical screening of Magnolia: the fruit fly pest - Suria Gisela Vásquez Morales (Polibotánica)
The fruit fly pest caused by Tephritidae severely affects fruit crops in the world. Integrated pest management includes the spraying of synthetic broad-spectrum insecticides. Due to the long-term negative effects of the use of synthetic insecticides, bioinsecticidal have been proposed as new ecological alternatives. In the study, the insecticide potential of Magnolia perezfarrerae, M. pugana and M. vovidesii was tested against Anastrepha ludens and A. obliqua. In addition, qualitative chemical analyses were carried out to explore the composition of insecticide-effectiveness extracts of sarcotesta of four species of Magnolia. Feeding bioassays in adult individuals consisted of a mixture of sugar and crude extracts of sarcotesta of Magnolia spp. Qualitative chemical profiles were performed using thin layer chromatography based on seven polarity systems. Moreover, secondary metabolite clusters were identified through qualitative analyses. The insecticide-effectiveness of Magnolia extracts was higher than 93% against A. ludens, whereas the effectiveness against A. obliqua ranged from 66% to 92% when M. perezfarrerae and M. vovidesii were used, respectively.  The extracts of Magnolia showed a wide variety of compounds with different polarity. Furthermore, the presence of alkaloids, flavonoids and phenols was detected in all species of Magnolia. The insecticide properties of Magnolia can contribute to the integrated management of Anastrepha.